Gambaran Status Metilasi Gen Promoter Methylguanine-deoksiribonucleic Acid Methyltransferase pada Astrositoma dan Faktor yang Memengaruhinya - KHAZATSIN, HADIO ALI (Indonesian Journal of Cancer, 2014)
Astrocytoma is the most common primary central nervous system tumor with difficult management as it requires acombination of surgery, chemotherapy and radiotherapy. This multimodalities approach increases patients survivalrate significantly, however chemotherapy resistance is now commonly seen. One of the potential causes of chemotherapyresistance is the epigenetic factors from O6 methylguanine-DNA-methyltransferase (MGMT) gene. MGMT gene has arole in DNA repair and also have a protective effect against exogenous and endogenous alkylation agents. The methylationof MGMT gene promoter leads to the decrease of MGMT protein, attenuating its function. Therefore, the methylationstatus of MGMT gene promoter can act as an indicator for astrocytomas progressivity and treatment progressivity.The aim of this study to determine the frequency of MGMT gene promoter methylation among patients withastrocytomas using methylation specific polymerase chain reaction (MS-PCR) and methylation sensitive highresolution melting (MS-HRM).Clinical data, imaging and parafin blocks from astrocytoma patients were collected in RSCM from 2008-2012. Themethylation status of MGMT gene promoter was confirmed using MS-PCR and MS-HRM. This is cross-sectional study.The total of 13 samples collected including 7 low-grade and 6 high-grade astrocytomas. The MGMT gene promoter wasmethylated in 1/13 cases using MS-PCR and 4/13 cases using MS-HRM. All methylated cases were low-gradeastrocytoma. There was significant association between the methylation status of MGMT gene promoter with thedegree of malignancy which is 4/7 samples hypermethylated in low-grade with no hypermethylation in high-gradeastrocytomas (p=0.049). While other factors like age, sex, karnofsky performance scale (KPS) and astrocytomas locationhave no significant association (p= 1,000; p= 0,657; p= 0,354; p= 0,538).The present study showed difference of methylation of MGMT gene promoter in astrocytomas with others studies whichis hypermethylated MGMT only found in low grade astrocytomas. Our study was the first to report the frequency ofMGMT promoter methylation among Indonesian astrocytoma patients.